ANALISIS YURIDIS PENGANGKATAN DAN PEMBERHENTIAN PERANGKAT DESA BERDASARKAN UNDANG-UNDANG NO 6 TAHUN 2014 TENTANG DESA: Legal Analysis Of The Appointment And Dismissal Of Village Officials Based On Law No. 6 Of 2014 Concerning Villages - Sarkawi, Sarkawi; Ashari, Ashari; Koynja, Johannes Johny (Ganec Swara, 2025)
The dismissal of village officials by the village head, which is within his authority, must also refer to the appropriate dismissal mechanism in its implementation.Based on The Indonesian Ombudsman's Report Settlement Management Information System that 2020-2023 shows that of the 947 public reports related to rural substances, A total of 375 reports or 40% of the reports received were reports regarding problems in the appointment and dismissal of village officials spread across several regions in Indonesia.The purpose of this research is to find out how the mechanism of appointment and dismissal of village officials in the legislation and legal protection of dismissed village officials. This research is a normative legal research that includes legal concepts related to the regulation of appointment and dismissal of village officials. This research uses a statutory, conceptual and case approach. The results of the research explain that the provisions for the appointment of village officials in the legislation are carried out with a selection stage of at least two prospective village officials who are consulted by the village head to the sub-district head as a representative of the regent or mayor while the mechanism for dismissal of village officials can be carried out by the village head when the village official has reached 60 years of age, is permanently incapacitated, no longer meets the requirements as a village official and violates the prohibition as a village official while the form of legal protection can be carried out through administrative efforts and administrative justice through state administrative courts